2022
DOI: 10.1080/14686996.2021.2025426
|View full text |Cite
|
Sign up to set email alerts
|

Topological alternation from structurally adaptable to mechanically stable crosslinked polymer

Abstract: Stimuli-responsive polymers with complicated but controllable shape-morphing behaviors are critically desirable in several engineering fields. Among the various shape-morphing materials, cross-linked polymers with exchangeable bonds in dynamic network topology can undergo on-demand geometric change via solid-state plasticity while maintaining the advantageous properties of cross-linked polymers. However, these dynamic polymers are susceptible to creep deformation that results in their dimensional instability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The flow activation energy provides insight into the temperature sensitivity of the network rearrangement, and changes in slope may either imply a change in mechanism for the exchange reaction or a change in the rearrangement-limiting process (cross-link exchange vs segmental dynamics). Evans has observed the latter scenario using measurements over a broad temperature range (200 °C) …”
Section: Theories and Established Relationshipsmentioning
confidence: 95%
See 1 more Smart Citation
“…The flow activation energy provides insight into the temperature sensitivity of the network rearrangement, and changes in slope may either imply a change in mechanism for the exchange reaction or a change in the rearrangement-limiting process (cross-link exchange vs segmental dynamics). Evans has observed the latter scenario using measurements over a broad temperature range (200 °C) …”
Section: Theories and Established Relationshipsmentioning
confidence: 95%
“…Techniques such as UV–vis absorption, fluorescence, Fourier-transform infrared spectroscopy (FTIR), gas or liquid chromatography (GC or LC), and nuclear magnetic resonance (NMR) are commonly used to quantify the rate ( k ) and/or extent ( K eq ) of bond formation, whereas rapid exchange processes at equilibrium can be measured using techniques such as variable temperature NMR (VT-NMR) or exchange spectroscopy (EXSY) (Figure ). In some cases, the extent of cross-link formation can be measured directly in the network using a solid-state technique like FTIR, , Raman, or ssNMR , spectroscopy.…”
Section: Theories and Established Relationshipsmentioning
confidence: 99%
“…Advanced woven fabrics reinforce soft body armor [6] and structural components [7]. Hu et al [8] reported promising results structurally adapting the mechanical performance of cross-linked polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the mechanical performance of polymeric composites is an aging and long-term deterioration subject [15][16][17][18] and requires further extensive investigation. In addition, the advanced composites raise the internal structure and component optimization problems, e.g., [3,8,13,14], requiring innovative design solutions and concepts.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of polymer materials and the continuous improvement of living standards, the requirements for matrix material properties are gradually becoming stricter. , Especially, the flame retardancy of materials has become an essential indicator due to frequent fire accidents in recent years . Extensive studies have found that there are the following three aspects that affect the efficiency of flame retardants in polymer materials: the types of flame retardant elements or groups in the molecular structure; particle sizes and dispersion forms in the polymer matrix; and the synergistic effect of different types of flame retardant groups. , In addition, the distributions of flame retardant groups at the molecular scale are also likely to affect the efficiency of flame retardants.…”
Section: Introductionmentioning
confidence: 99%